Early Childhood Education and Care Quality in the Socio-Economic Panel (SOEP) - the K2ID-SOEP Study - Christa Katharina Spieß; Pia S. Schober; Juliane F. Stahl (Jahrbücher für Nationalökonomie und Statistik, 2020)
Since 2000, Germany is experiencing an expansion of early childhood education and care (ECEC) institutions for children younger than three as well as increasing availability of full-day care for children aged three or older. More and more children attend ECEC centres for increasingly longer hours. Thus, ECEC centres are becoming an increasingly important environment for children and their parents. Given this background, an increasing number of economists are working on issues related to ECEC – with respect to either parental labour force participation or child outcomes. The K2ID-SOEP data sets are of particular interest to these researchers – and to all other social scientists investigating the impact of early childhood education and care across a variety of domains.The Socio-Economic-Panel Study (SOEP), as the largest and longest running multidisciplinary household panel in Germany (Wagner et0.167emal. 2007), started collecting information on ECEC centre attendance since its first wave in 1984. Irregularly, the SOEP collects information on the costs for ECEC care and the provider type. To learn more about the institutional context of ECEC, the aim of a larger research and data project funded by the Jacobs Foundation was to collect information from ECEC centres that are attended by children in the SOEP. Moreover this information of an institution survey was combined with the individual data of the SOEP. 1 This approach, which takes individual data as a starting point, differs from other data sets that collect comparable information in ECEC centres, such as the National Education Panel Study (NEPS), NEPS-starting cohort 2 (e.0.167emg. Blossfeld et0.167emal. 2011), which started with a sample of ECEC centres and planned to followed all children in the centres. The main aim of our K2ID-SOEP study (short: K2ID-SOEP) was to collect information on the quality of ECEC centres of all SOEP children in such centres. ECEC quality is a key feature that affects child development and other parental outcomes, such as parental employment and parental wellbeing (see e.0.167emg., Schober et0.167emal. 2016; Anders 2013). The K2ID-SOEP study was realized between 2013 and 2015. K2ID is an acronym for `Kinder und Kitas In Deutschland' (`Children and Childcare Centres in Germany). The K2ID-SOEP study encompasses two surveys, a Parent Survey and an Institution Survey.
Keywords: 330